1999
DOI: 10.1063/1.370346
|View full text |Cite
|
Sign up to set email alerts
|

In-plane magnetic anisotropy in CoCrPt and CoCrTa films deposited onto patterned silicon substrates

Abstract: Topographically induced in-plane magnetic anisotropy has been observed in CoCrTa and CoCrPt films deposited onto oxidized silicon substrates which are lithographically patterned with fine grooves of period 200–320 nm and amplitude 20–50 nm. The coercivity and remanence are higher parallel to the grooves. Anisotropy has been observed in both rf- and dc-magnetron sputtered films with a (112̄0) preferred orientation, which is achieved by growth at elevated temperature on a (200)-oriented Cr underlayer at low base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In order to analyse our experimental results it is rather convenient to consider only the shape anisotropy due to the soft magnetic character of the samples. It is well known that continuous thin films of Ni and permalloy do not develop in-plane magnetic anisotropy [16]. However, as shown in figures 2(a) and (b), different resonant fields are observed in the parallel and perpendicular configurations (see figure 1) indicating the existence of an in-plane easy axis along the direction of the stripes' axes.…”
Section: Resultsmentioning
confidence: 87%
“…In order to analyse our experimental results it is rather convenient to consider only the shape anisotropy due to the soft magnetic character of the samples. It is well known that continuous thin films of Ni and permalloy do not develop in-plane magnetic anisotropy [16]. However, as shown in figures 2(a) and (b), different resonant fields are observed in the parallel and perpendicular configurations (see figure 1) indicating the existence of an in-plane easy axis along the direction of the stripes' axes.…”
Section: Resultsmentioning
confidence: 87%
“…The underlying physical mechanism responsible for the difference in circumferential -direction) and radial -direction) coercivites, , is likely a combination of several factors [2]. It is assumed here that these can be adequately accounted for in the LLG model with a Gaussian distribution of grain anisotropy axes, where a mean angular direction and standard deviation are specified.…”
Section: Micromagnetic Recording Modelmentioning
confidence: 99%
“…Planar oriented media [2] is of interest for a number of reasons. These include the possibility of improved thermal stability, DC noise and track edge definition [3]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…In these previous attempts at self-assembly, however, the nanoparticle superlattices obtained were usually highly symmetric structures, such as close-packed sixfold hexagonal lattices, fourfold cubic square lattices, and threefold quasi-honeycomb lattices. To enhance the versatility of nanoparticle superlattices, more complex and low symmetry ordered structures are also strongly desired, especially in the case of magnetic materials, where it has been reported that the magnetic reversal and magneto-transport properties are strongly affected by the symmetry of the lattice arrangements, and the presence of anisotropic periodic grooves or surface scratches can enhance the coercivity and remanent fields . For structural control of nanoparticle assembly, various procedures have been proposed, such as utilization of anisotropic nanoscale templates, ,, the application of external magnetic fields, the tuning of interligand interactions, , the hybridization of multiple-sized nanoparticles, and the utilization of nonspherical (cubic or rod-like) nanoparticles. Nevertheless, to our knowledge, the spontaneous self-assembly of single-sized spherical nanoparticles into low-symmetry structures, such as twofold symmetric rectangular nanoparticle superlattices, with long-range periodic order has never been established.…”
Section: Introductionmentioning
confidence: 99%